MEMBANGUN SOLIDARITAS SOSIAL UNTUK MENCIPTAKAN KEKELUARGAAN - Rahman, Ahmad Syafii; Kuncoro, Kuncoro (Gemi: Jurnal Penelitian dan Pengabdian, 2022)
Gegulu Hamlet is a hamlet located in Gulurejo Village, Lendah District, Kulon Progo Regency. Gegulu Hamlet is one of the hamlets in Gulurejo Village which is the location of the Group 5 Regular Real Work Lecture. The results are for personal consumption as well as opportunities for the livelihoods of the surrounding community. In addition, many people own livestock, rice fields, and gardens to increase their personal income. The 20 sub-districts that had the highest average monthly rainfall in 2016 were in Samigaluh District of 364 mm with a total of 12 rainy days per month. The rainfall in Kulon Progo Regency fluctuates from year to year. In addition, there is no health service post that has adequate road access in Gegulu Hamlet, Gulurejo Village, Lendah District, Kulon Progo Regency, Yogyakarta.